"Tu lucha es mi lucha": Teaching Spanish through an equity and social justice lens. (29th September 2021) - Di Stefano, Marialuisa; Almazán‐Vázquez, Abelardo; Yepes‐Amaya, William; Britton, Emma Razifard
Abstract: This article reports about a 2‐year participatory action research (PAR) study in which three instructors engaged in an ongoing PAR cycle to develop and implement an explicit social justice teaching approach in their differing instructional contexts in the Northeastern US: a graduate course for teacher education and two secondary school Spanish courses. Building upon critical pedagogy (Freire,  2005) and intersectional positionalities studies (Crenshaw,  1989) and engaging in a collaborative self‐study research with the fourth author, the team reflected on the emergence of stereotypes related to gender, race, language, immigration, and nationality in the language classroom. Results suggest that: (a) students' identities seem reaffirmed from scaffolded instruction that includes authentic materials (b) instructors, as role models, can influence students' identity development and activism engagement. Implications include a series of recommendations for justice‐oriented instructional strategies and assessments for the secondary school Spanish curriculum and teacher education. The Challenge: Stereotypes related to the gender, race, language, immigration, and nationality of Latinx/Latiné identities continue to emerge in the Spanish classrooms in the United States. How can educators recognize such stereotypes, commit to dismantling them, and enhance both students' and teachers' disposition to embrace their intersectional identities and engage in civil activism?